Report of the National Seminar Organised By Planning Commission in Collaboration with Maharashtra Government on Liquidation of Illiteracy Held at Poona on November 7, 8, 9 and 10, 1965 - Planning Commission (Planning Commission, 1967)
The National Seminar on the Liquidation of Illiteracy (1965) and subsequent adult literacy initiatives highlighted the critical challenge of illiteracy in India, particularly among rural adults and women. With over 73% of adults illiterate, the seminar emphasized functional literacy, integrating reading and writing skills with socio-economic engagement. Successful models, such as Maharashtra’s Gram Shikshan Mohim, demonstrated the effectiveness of mobilizing local communities and volunteers. Challenges identified included poverty, lack of motivation, inadequate resources, and limited government prioritization. Proposed strategies included pre- and post-literacy programs, pilot projects, library networks, and active participation of educational institutions and literate citizens. The seminar and related initiatives underscored the necessity of structured administration, adequate financing, and continuous evaluation to ensure sustainable adult education, making literacy a cornerstone for India’s socio-economic development.
Government of India Planning Commission New Delhi
Government of India Planning Commission New Delhi
Keywords: Adult Literacy; Liquidation of Illiteracy; Planning Commission of India; Gram Shikshan Mohim; Functional Literacy; Rural Education; Literacy Campaigns; Public Cooperation; Literacy Financing; Non-Formal Education